Learning by Doing: A Daily Life Study of Principal Interns' Leadership Activities During the School Year. (March 2022) - Drake, Timothy A.
Clinical experiences, including the full-time principal internship, are considered to be one of the most important components in principal preparation. Yet research on the principal internship is limited to surveys and interviews. I use a daily life methodology to explore full-time principal interns' experiences during an academic school year. I find that interns' activities approximate the work of a school principal in many aspects of the job, including administrative activities and instructional leadership. I also find that variation between interns' activities is consistent with the literature, in that their activities vary based on personal background and school context.